Tailored Double Emulsions Made Simple. Issue 5 (6th December 2021) - Wang, Junwei; Hahn, Simon; Amstad, Esther; Vogel, Nicolas
Abstract: Double emulsions, such as water‐in‐oil‐in‐water droplets, are important material platforms for conducting fundamental research and for technological applications. To date, well‐defined double‐emulsion droplets consisting of a single water core and a thin oil shell can be exclusively formed with sophisticated microfluidic devices. The fabrication, preparation, and operation of such devices is challenging, which reduces the availability of tailored double emulsions to a limited community of experts. Here, a simple method is introduced to produce single‐core double emulsions with high yield in large quantities, using a vortex mixer. Utilizing the density difference between the dispersed droplet and the continuous phase, this two‐step emulsification method can achieve very small core droplet diameters below 10 μm and ultrathin shells with thicknesses below 1 μm. A detailed picture of the formation mechanism is provided and it is demonstrated that the process can be extended to produce multishell and multicore emulsions. Finally, its application is demonstrated to produce structurally colored colloidal supraparticles with unprecedented uniformity and yield. The method allows the creation of tailored double emulsions with minimal time, cost, effort, and expertise, and may widen its application to nonspecialized scientific communities. Abstract : A simple method is developed to produce double emulsions of a single core and a thin shell at a milliliter per minute production rate, requiring minimal instrumentation, cost, and expertise. This two‐step emulsification technique offers control of shell thickness, diversity of liquid formulations, integration with microfluidic devices, and potential to scale‐up.